Learning Direct and Inverse Proportion Using Musi Tour - Nursa Fatri Nofriati; Yusuf Hartono; Somakim Somakim (International Journal on Emerging Mathematics Education, 2019)
This study used design research to produce learning trajectory through Musi Tour context which can help students in understanding the concept of direct and inverse proportion. This study used PMRI approach. The object of this study was the seventh grade students of SMP Nurul Qomar Palembang. Data for retrospective analysis was collected from teaching experiment in the form of students’ work results, field notes, and students’ interview. The results obtained in this study were learning trajectory which consisted of 3 activities: 1) students were given contextual problems namely Musi Tour as the starting point in learning direct and inverse proportion. 2) through students' understanding of the ratio table in the Musi Tour context, students can understand the direct proportion. 3) students can model and understand the concept of inverse proportion and solve the problems by using Ratio table. The results showed that the use of Musi tour context can help students in understanding the concept of direct and inverse proportion.